Serum Progesterone, Oestradiol-17β, FSH and LH levels in Anestrus Surti buffaloes treated with Ovsynch alone and in combination with PRID - Savani, HR; Khasatiya, CT; Saxena, Swati; Patel, SB; Singh, VK (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
This study was carried out on 18 postpartum anestrus Surti buffaloes, divided into three equal groups (6 in each) to evaluate the serum progesterone, oestradiol-17β, FSH and LH concentrations (by ELISA) before, during and after Ovsynch and Ovsynch + PRID protocols. Six anestrus buffaloes each were treated with standard Ovsynch protocol (T1) and Ovsynch along with PRID (Progesterone releasing intravaginal device) protocol (T2) with fixed-time AI (FTAI). Six anestrus buffaloes were kept as untreated control (T3). Blood samples were obtained from the animals on day 0 (before treatment), day 4 (during treatment), day 8 (after PGF2α injection), day of induced estrus/FTAI and day 18 post-AI (after treatment). The mean serum progesterone level on day 4 was significantly (p<0.01) higher in the T2 group as compared to T1 and T3 groups, while the level on day 8 was significantly (p<0.01) higher in both the treatment groups (T1 & T2) as compared to control group, however there was no significant difference (p>0.05) on the day of estrus between three groups. The mean serum oestradiol-17β and follicle stimulating hormone (FSH) levels on 8th day were significantly higher (p<0.01) in both the treatment groups (T1 and T2) as compared to control group (T3). However, there was no significant difference on day 0, 4, day of estrus and day 18 post-AI between groups. The mean serum luteinizing hormone (LH) levels of acyclic buffaloes were not found significantly different (p>0.05) among days in any of the treatment and control groups. But the mean LH concentration on the day of estrus in the T1, T2 & T3 was significantly higher (p<0.01) and thereafter decreased markedly on 18th day post-AI in all the groups. The conception rates at FTAI/first estrus in three groups were 66.66%, 50.00% and 75.00%, respectively.